Migraine and Autonomic Nervous System Dysfunction - J. Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Tests of autonomic nervous system (ANS) function were administered to 80 adult patients with migraine (28 with disabling headaches) and 85 matched controls, in a study at the Thomas Jefferson University Hospital, Philadelphia, PA, Johns Hopkins School of Hygiene and Public Health, Albert Einstein College of Medicine, and Montefiore Medical Center, Bronx, NY.